Transformation of the Old Russian heritage in the sphere of state authority and administration in the Grand Duchy of Lithuania - Tsemushau, Stsiapan N. (Journal of the Belarusian State University. History, 2025)
This article examines issues related to the transformation of the Old Russian heritage in the socio-political life of the Grand Duchy of Lithuania, identifying differences in the social and political spheres of the Grand Duchy of Lithuania and neighbouring states, and determining the forms and methods of borrowing elements, mechanisms, and traditions of public administration in the Grand Duchy of Lithuania from the Grand Duchy of Moscow and the Kingdom of Poland. It is noted that it is of fundamental importance to point out the decisive role of the Old Russian heritage in the sphere of organising power and governance in the Grand Duchy of Lithuania, which over time underwent a transformation due to the influence of the peculiarities of the internal political situation and external influences.
Keywords: Ancient Rus’; Grand Duchy of Moscow; Russian state; Grand Duchy of Lithuania; public administration; supreme power; state institutions; tradition; transformation